Postintensive care syndrome family: A comprehensive review - Kasumi Shirasaki; Toru Hifumi; Nobuto Nakanishi; Nobuyuki Nosaka; Kyohei Miyamoto; Miyuki H. Komachi; Junpei Haruna; Shigeaki Inoue; Norio Otani (Acute Medicine & Surgery)
Abstract Families of critically ill patients are predisposed to tremendous burdens when their relatives are admitted to the intensive care unit (ICU). Postintensive care syndrome family (PICS‐F) can be described as a devastated life, encompassing psychological, physical, and socioeconomical burdens that begin with the emotional impact experienced by the family when the patient is admitted to the ICU. PICS‐F was primarily proposed as a clinically significant psychological impairment, but it needs to be extended beyond the psychological impairment of the family to include physical and socioeconomical impairments in the future. The prevalence of physiological problems including depression, anxiety and post‐traumatic syndrome is 20–40%, and that of non‐physiological problems including fatigue is 15% at 6 months after the ICU stay. Assessment of PICS‐F was frequently conducted at 3‐ or 6‐month points, although the beginning of the evaluation was based on different assessment points among each of the studies. Families of ICU patients need to be given and understand accurate information, such as the patient's diagnosis, planned care, and prognosis. Prevention of PICS‐F requires a continuous bundle of multifaceted and/or multidisciplinary interventions including providing a family information leaflet, ICU diary, communication facilitators, supportive grief care, and follow‐up, for the patient and families from during the ICU stay to after discharge from the ICU. This is the first comprehensive review of PICS‐F to address the concept, risk factors, assessment tools, prevalence, and management to prevent PICS‐F to facilitate acute care physicians' understanding of PICS‐F.